FORM OF EVALUATION OF NEWS TEXT LEARNING AT SMP NEGERI 2 JAKARTA - Putri, Irena Aprilia; Boeriswati, Endry; Supriyana, Asep (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to describe the form of evaluation in learning Indonesian, especially on news text material at SMP Negeri 2 Jakarta. The method used is a quantitative descriptive approach with data collection in the form of closed data collection techniques, observation, and interviews. The results of the study showed that most students understand the elements and structure of news texts and are able to write simple news, although some still have difficulty distinguishing facts and opinions. The learning evaluation carried out by the teacher includes written evaluations, project or performance evaluations and group presentations. This evaluation is considered quite effective in encouraging student involvement, but teachers still need to adjust the evaluation method to the diverse learning styles of students. Therefore, this study will provide a solution regarding the appropriate form of evaluation to be applied to news text learning at the junior high school level.